2004
DOI: 10.1093/humrep/deh177
|View full text |Cite
|
Sign up to set email alerts
|

Case report: successful pregnancy after vitrification of a human blastocyst that had completely escaped from the zona pellucida on day 6

Abstract: This case report describes a successful pregnancy after vitrification of a human hatched blastocyst. A 31-year-old woman, after failed stimulated and thaw cycles, underwent short-treatment protocol stimulation, and oocytes were recovered transvaginally with ultrasound guidance. Eight mature oocytes were obtained and six were fertilized with conventional IVF. Consecutive embryo transfer was performed, in which two cleaved embryos were transferred on day 3 and a single blastocyst was transferred on day 5, but no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…Several studies on mammalian embryos have proven that the best tool for vitrification is cryotop [28,[34][35][36]. In the Zhang study [36], the vitrified mouse embryos derived in vivo with cryotop showed survival rates of 96 % for two-cell vitrified embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies on mammalian embryos have proven that the best tool for vitrification is cryotop [28,[34][35][36]. In the Zhang study [36], the vitrified mouse embryos derived in vivo with cryotop showed survival rates of 96 % for two-cell vitrified embryos.…”
Section: Discussionmentioning
confidence: 99%
“…With the improvement of culture systems and blastocyst cryopreservation techniques, some pregnancies are achieved following the transfer of cryopreserved day-7 zona-intact blastocysts [13][14][15], re-cryopreserved day-7 zona intact blastocysts [16], and day-5 and day-6 spontaneously hatched blastocysts [17][18][19][20]. However, as far as is known, there are no reports on pregnancies following the transfer of re-cryopreserved day-7 spontaneously hatched blastocysts.…”
Section: Introductionmentioning
confidence: 99%
“…Many research studies have been focused on vitrification due to significantly higher survival and pregnancy rates observed. The pregnancy rate and survival rate are reported as 37-48% and 70-95%, respectively [7,[21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%